2016
DOI: 10.1175/waf-d-16-0086.1
|View full text |Cite
|
Sign up to set email alerts
|

Composite Environments of Severe and Nonsevere High-Shear, Low-CAPE Convective Events

Abstract: Severe convection occurring in environments characterized by large amounts of vertical wind shear and limited instability (high-shear, low-CAPE, or “HSLC,” environments) represents a considerable forecasting and nowcasting challenge. Of particular concern, NWS products associated with HSLC convection have low probability of detection and high false alarm rates. Past studies of HSLC convection have examined features associated with single cases; the present work, through composites of numerous cases, illustrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 51 publications
12
59
0
Order By: Relevance
“…The environments shown in this study are somewhat similar to high-shear, low-CAPE (HSLC) environments that mainly appear for the cool season tornadoes in the southeastern US (Sherburn and Parker 2014;Sherburn et al 2016). Sherburn et al (2016) examined the composite HSLC environments and showed that the forcing of ascents for severe events were stronger than that for nonsevere events, which is similar to our results in MAM and DJF.…”
Section: Seasonality Of Tornadic Extratropical Cyclonessupporting
confidence: 85%
“…The environments shown in this study are somewhat similar to high-shear, low-CAPE (HSLC) environments that mainly appear for the cool season tornadoes in the southeastern US (Sherburn and Parker 2014;Sherburn et al 2016). Sherburn et al (2016) examined the composite HSLC environments and showed that the forcing of ascents for severe events were stronger than that for nonsevere events, which is similar to our results in MAM and DJF.…”
Section: Seasonality Of Tornadic Extratropical Cyclonessupporting
confidence: 85%
“…The freezing process releases more latent heat to stimulate convection, allowing more ice particles to participate in the electrification process of collision and separation, thereby enhancing lightning activity (Khain et al, 2008;Mansell and Ziegler, 2013;P. Zhao et al, 2015;Shi et al, 2015). A similar enhancement in lightning activity due to aerosols was also found in oceanic regions, where aerosols and their precursors discharged by ships significantly enhanced lightning activity over shipping lanes (Thornton et al, 2017).…”
Section: Introductionmentioning
confidence: 74%
“…Although this might be counter to what one would expect, the cool season events considered here also have higher EF ratings than do the warm season events (Figure 5c). Note that "cool season" and "warm season" are defined simply by date, rather than by storm environments (e.g., as in Sherburn et al, 2016, who associated cool season tornado events with relatively low convective available potential energy and high vertical wind shear). In terms of storm morphology, we find somewhat expected results, with QLCS tornadoes (generally) having lower EF ratings ( Figure 5c) and thus smaller OTAs (Figure 5b) than supercellular tornadoes (see also Figure 3).…”
Section: 1029/2019gl084099mentioning
confidence: 99%